Television director’s skill in the formation of socio-cultural values of a viewer - A. Aidar, T. Kabiyeva,; Zor, L.; Zhumankulova, Y. (Opción, 2019)
The study aims to investigate the artistic skills of a television director in the formation of the socio-cultural values of a TV viewer via the historical-comparative method, the analysis of Kazakhstani TV programs and the comparative a:nalysis of the world models of TV documentary projects. As a result, the director of documentary films should observe, absorb information and pay attention to people and scenes. In conclusion, empathy combines the ability not only to think about the position of the hero but also to feel his problems and his experience.